Effect of low-intensity pulsed ultrasound on regenerative potential of transplanted ASCs –PCL construct in articular cartilage defects in sheep - VAHEDI, PARVIZ; ROSHANGAR, LEILA; JAROLMASJED, SEYEDHOSEIN; SHAFAEI, HAJAR; SAMADI, NASSER; SOLEIMANIRAD, JAFAR (The Indian Journal of Animal Sciences, 2016)
Articular cartilage is affected by weight loading and mechanical stimuli. Low intensity ultrasound promotes chondrogenesis in cartilage injury. This study was designed to show the effect of low-intensity pulsed ultrasound on chondrogenesis potential of transplanted adipose derived stem cells- polycaprolactone (ASCs –PCL) construct in vivo.The adipose tissue was obtained from infrapatellar fat pad of 5 male sheep. Adipose tissue derived stem cells (ASCs) at passage 2 were seeded in polycaprolactone (PCL). The cartilage defects were created on both sides of distal femoral articular cartilage. The right joint was chosen as control group. The left joint was chosen as experimental group and was exposed to low-intensity pulsed ultrasound with intensity 200 mW/cm², 10 min/day for 6 weeks. After 6 months, animals were euthanized to retrieve repaired articular cartilage tissue. Macroscopic appearance of defects was examined and samples of repaired cartilage tissue were analyzed by real time RT-PCR. The results showed that in the treated group with-LIPUS, cartilage defects were totally filled with relatively thin amorphous proliferative tissue and in the control group the defects were left as a dimple in the cartilage defects. Real time RT-PCR analysis showed that cartilage-specific genes expression levels are significantly increased by application of LIPUS after transplantation of ASCs-PCL construct in vivo. The results suggested that low-intensity pulsed ultrasound stimulates ASCs differentiation and induces chondrogenesis at the ASCs-PCL construct in in vivo.